Absorption based solid state hydrogen storage system: A review. (August 2022) - Kumar, Alok; Muthukumar, P.; Sharma, Pratibha; Kumar, E. Anil
Highlights: Reviewed absorption based solid state hydrogen storage materials. Alloy tailoring and absorption/desorption characteristics of intermetallic alloys. Alloy synthesis, structure and decomposition thermodynamics of Complex Hydrides. Regeneration & reversible characteristics of absorption based hydrogen storage alloy. Abstract: To run a sustainable society, hydrogen is considered as one of the most reliable option for clean and carbon free energy carrier. Hydrogen can be produced through several means using renewable energy sources, and can be stored either in solid, liquid or gaseous state. Though, compressed and liquefied hydrogen storages are well-established technologies in the commercial sector, however, due to the leakage risk, boil-off losses and explosive nature, world is exploring a safer way of hydrogen storage i.e. absorption/adsorption based solid-state hydrogen storage technology. The present review focuses mainly on the different material options available for the absorption based solid state hydrogen storage technology. The study reports insight view of different absorption material, broadly classified as metal hydrides and complex hydrides, with their hydrogen storage and reversible characteristics. The review also reports the tailoring properties of different hydrogen storage alloys and effect of element substitution on the absorption/desorption characteristics of a particular alloy. Key issues like effect of ball milling, annealing, doping, grain size, etc., on the alloy synthesis have been addressed. The review broadly summarizes the progress and recent worldwide advancement in the absorption based solid state hydrogen storage materials, synthesis and their hydrogenation/dehydrogenation mechanisms.